Processing macroeconomic signals: Voter responses to growth, unemployment, inflation and stock markets - Love Christensen; Mikael Persson; Jana Schwenk (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2025)
Economic voting theory suggests that voters reward incumbents for strong economic performance and punish them for weak performance. However, this view often ignores the multidimensional nature of the economy. Hence, we lack systematic evidence about how voters simultaneously process multiple economic signals. This study provides a comprehensive examination of how voters respond to four key economic dimensions: growth, unemployment, inflation, and stock markets. We develop a theoretical framework distinguishing between different types of economic reasoning: macroeconomic, egotropic, sociotropic, and distributive reasoning. We first use descriptive data from OECD countries to understand the economy's dimensionality and analyze survey data from national election studies to assess the impact on economic evaluations. Finally, we present findings from survey experiments conducted in Germany, Sweden, and the United States, tailored to analyze the impact of the four economic dimensions in an ideal information setting. Our results reveal interesting patterns in how voters process economic information. Voters can discern relationships between economic dimensions and their effects on personal and economic circumstances, and distributional outcomes. Subsequently, all four signals independently affect preferences for economic policy and voting intentions. Inflation emerges as a dominant factor, shaping personal and national economic evaluations. Our findings challenge traditional approaches to economic voting by exploring how voters integrate multiple economic signals. By emphasizing the multidimensionality of economic signals, we highlight implications for democratic accountability.
Keywords: 330